Bomba, Trapiche y Son: identificar el sonido autóctono de la cultura musical afro choteña, desarrollando una producción de 3 temas tradicionales del género musical ecuatoriano bomba - Vásquez Castillo, Santiago Renán (2018)
Within the popular Ecuadorian music, we can find one of the musical genres that has had the most acceptance inside and outside of the country, due to the cultural recognition that the Afro-Choteña population has had in Ecuador, specifically in the area of Imbabura and Carchi. Speaking of “Bomba” music, is to understand the cultural roots embodied through the drum, the guitar, the requinto, the dance, the poetry and other elements that make the “Bomba” music a whole. This cultural manifestation stems from the need of liberation of the Afro-American people, a liberation that was not allowed by those patrons. The Ecuadorian Bomba is a musical genre that shows certain characteristics or elements that make this rhythm very meaningful, very danceable and sometimes joyful. It is true that in recent years there has been many productions with this rhythm that has reached high points in popularity, however, within this musical style there is a traditional repertoire for the Chota Valley Communities which has stayed in the musical memories of those singers, poets, interpreters and pioneers of the Bomba who are in need of maintaining their traditions with those lyrics. For this reason, this project will focus on rescuing the traditional repertoire of the Afro- American people and exposing them in a production of 3 songs where the characteristic elements of the Bomba music are identified as: its instrumentation, interpretation, lyrics and musical structures. A series of videos have been added and will be presented by interpreting the instruments involved in this genre with their respective variations and characteristics. These will produce the native and original sounds of the Bomba music as evidenced.